Britain, détente, and changing East-West relations - White, Brian, 1947- (Routledge, 1992)
Argues that Britain's contribution to East-West detente has been consistently undervalued. Re-evaluates Britain's role in the post-war world and provides a valuable case study in foreign policy formulation and implementation.
Keywords: World politics -- 1945-1989.; East and West.; Detente.; Great Britain -- Foreign relations -- 1945-; Politique mondiale -- 1945-1989.; Détente (Politique); Grande-Bretagne -- Relations extérieures -- 1945-; POLITICAL SCIENCE -- Government -- International.; POLITICAL SCIENCE -- International Relations -- General.; Detente; East and West; Diplomatic relations; World politics; Great Britain; Ost-West-Konflikt; Geschichte; Großbritannien; DETENTE.; UNITED KINGDOM.; EAST-WEST RELATIONS.; Since 1945; Foreign relations